2000
DOI: 10.1007/s004670000443
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for urolithiasis in children on the ketogenic diet

Abstract: Kidney stones have been associated with use of the ketogenic diet in children with refractory seizure disorders. We performed a case-control study examining risk factors for the development of stones on the ketogenic diet, and prospectively followed children initiating the ketogenic diet to evaluate the incidence of urolithiasis. Clinical characteristics of 18 children presenting with stones (8 uric acid stones, 6 mixed calcium/uric acid stones, 1 calcium oxalate/phosphate stone, 3 stones not evaluated) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
1
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(135 citation statements)
references
References 7 publications
(7 reference statements)
4
121
1
9
Order By: Relevance
“…In addition to the age factor, the presence of hypercalciuria also increases the risk for the development of kidney stones [44]. Uric acid, calcium oxalate, calcium phosphate or mixed composition stones have been reported in up to 7% of children on the KD [44][45][46].…”
Section: Kidney Stonesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the age factor, the presence of hypercalciuria also increases the risk for the development of kidney stones [44]. Uric acid, calcium oxalate, calcium phosphate or mixed composition stones have been reported in up to 7% of children on the KD [44][45][46].…”
Section: Kidney Stonesmentioning
confidence: 99%
“…Uric acid, calcium oxalate, calcium phosphate or mixed composition stones have been reported in up to 7% of children on the KD [44][45][46]. Risk may be higher with long-term treatment [29] and concurrent use of carbonic anhydrase inhibitors [47].…”
Section: Kidney Stonesmentioning
confidence: 99%
“…Even though efficacy and safety have been demonstrated in several studies over the past decade [1][2][3][4], GI intolerability and various other complications have limited its use in many patients [5][6][7][8][9]. A high-fat diet prolongs gastric emptying time and can cause vomiting, especially in patients with gastroesophageal reflux [12].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its potent antiepileptic efficacy, wide application of the KD for long-term maintenance has been limited in some children by poor tolerability [5][6][7][8]. Significant numbers of patients suffer from GI discomfort during KD treatment, in addition to its unpalatability [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiologic studies have suggested that low water intake, 1 high protein diets, 2,3 and ketogenic diets [4][5][6] are all associated with increased risk of urolithiasis in the general population. Although these and other factors may be important risk factors in G-tube fed (GTF) children, previous studies have not specifically examined possible associations.…”
Section: Methodsmentioning
confidence: 99%